Investigation of ammonium- And phosphonium-based deep eutectic solvents as electrolytes for a non-aqueous all-vanadium redox cell - Bahadori, L.; Hashim, Mohd Ali; Manan, N.S.A.; Mjalli, F.S.; AlNashef, I.M.; Brandon, N.P.; Chakrabarti, M.H. (Electrochemical Society, 2016)
The charge/discharge characteristics for vanadium acetylacetonate in deep eutectic solvents were evaluated using an H-cell with an anion-exchange membrane separator for the first time. Coulombic (CE) and energy efficiencies (EE) of the electrolyte containing V(acac)3/0.5 M TEABF4 in DES3 (a hydrogen bonded eutectic between choline chloride and ethylene glycol) were obtained as 49-52% and 25-31%, respectively, when charging from 0 to 50% of theoretical maximum state-of-charge for 12 cycles. The low CE may be due to the crossover of the active species through the separator, or to the loss of active vanadium due to a parasitic reaction. However, the CE was similar to that for acetonitrile (CH3CN) indicating the promise of DESs as suitable electrolytes for future evaluation. Charge and discharge voltages are respectively higher and lower than the formal cell potential obtained by voltammetry. Ohmic drop in the DES results from the low conductivity of the electrolyte and the relatively large distance between the two electrodes in the H-cell. Further studies require investigation in a flow cell with analyses of polarization curves and impedance to determine the loss mechanisms in sufficient detail.